CORRECTION OF HYPODINAMY AS A FACTOR OF THE RISK OF OBESITY DEVELOPMENT IN FIRE-RESCUERS - E. V. BURDYUKOVA; A. N. ARKHANGELSKAYA; S. N. ALEKSEENKO; I. A. YAKIREVICH; E. A. DMITRIEVA; O. P. KARAZHELYASKOV; M. V. IVKINA; K. G. GUREVICH (Кубанский научный медицинский вестник, 2018)
Aim. To evaluate the effectiveness of the developed special sports complex in the prevention of hypodynamia and obesity among firefighters-rescuers.Materials and methods. A survey of 490 men with no history of chronic infectious and non-infectious diseases aged 20-59 was conducted. 328 people were the main group, 162 people were the control group. The baseline data included anthropometric development indicators, bioimpedance test results, the extraction of biochemical blood test results; the body mass index (BMI) and the ratio of waist and hip circumference were determined. A questionnaire was conducted to identify hypodynamia (according to the IPAQ questionnaire) and the nutrition structure (according to the questionnaire on the food label literacy questionnaire, past). Both questionnaires were adapted to the Russian Federation. Statistica for Windows 8.0 was used for statistical processing. We used a comparison of the means of the Student method. To compare the values expressed in percent, the method of inverse trigonometric Fisher transformations was used.Results. We have developed and proposed for firefighters-rescuers, included in the main group, special sports complexes, which were used for 6 months. These complexes represent additional physical training by the developed method. There are two of them: one with an emphasis on the prevention and rehabilitation of people with osteochondrosis of the lumbar spine, and the other for cervical and thoracic localization, including with a syndrome of shoulder-scapular periarthritis.Classes were held 3 times a week, the duration of 1 session was 45-50 minutes. The choice of the complex was carried out at the request of firefighters-rescuers. The first complex was selected by 52 people. Based on the results of the study, against the background of the use of sports complexes, there was a 2-fold decrease in the incidence of obesity. Such a high efficiency is due to the fact that obesity of the I degree prevailed among the firefighters-rescuers. In addition, the frequency of occurrence of dyslipidemia, hyperglycemia, and hypodynamia decreased.Conclusion. The use of this sports complex can reduce the risk factors for development of disability among rescue firefighters by preventing hypodynamia and reducing the incidence of hyperglycemia and dyslipidemia, as factors in the development of obesity.